2022
DOI: 10.3390/ijerph19148747
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents, Young Adults, and Adults Continue to Use E-Cigarette Devices and Flavors Two Years after FDA Discretionary Enforcement

Abstract: This study assesses the use of e-cigarette devices and flavors using a large, cross-sectional survey of adolescents, young adults, and adults (N = 6131; ages 13–40 years old; Mage = 21.9) conducted from November to December 2021, 22 months after the FDA announced its prioritized enforcement policy against some flavored pod/cartridge-based e-cigarettes. We analyzed the patterns of use by age group: adolescents and young adults (AYAs) under 21 (minimum age of e-cigarette sales), young adults (21–24 years old), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…A growing body of research demonstrates the role of policy comprehensiveness. While federal flavor policies have reduced tobacco product use and sales overall, menthol exemptions and major product exemptions in these policies have been followed by increased sales and use of exempted flavors and products and widened disparities 5–7,19. At the state and local levels, studies evaluating the impact of FTP sales restrictions have found that more comprehensive policies reduced flavored tobacco availability, advertising, and sales to a greater extent than less comprehensive policies 13–15.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A growing body of research demonstrates the role of policy comprehensiveness. While federal flavor policies have reduced tobacco product use and sales overall, menthol exemptions and major product exemptions in these policies have been followed by increased sales and use of exempted flavors and products and widened disparities 5–7,19. At the state and local levels, studies evaluating the impact of FTP sales restrictions have found that more comprehensive policies reduced flavored tobacco availability, advertising, and sales to a greater extent than less comprehensive policies 13–15.…”
Section: Discussionmentioning
confidence: 99%
“…While federal flavor policies have reduced tobacco product use and sales overall, menthol exemptions and major product exemptions in these policies have been followed by increased sales and use of exempted flavors and products and widened disparities. [5][6][7]19 At the state and local levels, studies evaluating the impact of FTP sales restrictions have found that more comprehensive policies reduced flavored tobacco availability, advertising, and sales to a greater extent than less comprehensive policies. [13][14][15] In several jurisdictions, retailer exemptions such as those for adult-only and tobacco-only retailers have led to increased tobacco retailer density, increased disparities in flavored tobacco access, policy enforcement challenges, and continued flavored tobacco advertisement exposure in convenience stores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently e-cigarette use is at an all-time high both in adolescents and adults [ 8 ], while the vaping epidemic continues with the public being largely unaware of the detrimental effects of using new nicotine-containing products. Moreover, tobacco companies continue to introduce newer products with taglines such as “safer alternatives” or “less harmful” that are designed to have public appeal.…”
Section: Introductionmentioning
confidence: 99%